The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1088/1758-5090/9/1/015006
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinting of functional human skin: production and in vivo analysis

Abstract: Abstract. Significant progress has been made over the past 25 years in the development of in vitro-engineered substitutes that mimic human skin, either to be used as grafts for the replacement of lost skin, or for the establishment of in vitro human skin models. In this sense, laboratory-grown skin substitutes containing dermal and epidermal components offer a promising approach to skin engineering. In particular, a human plasma-based bilayered skin generated by our group, has been applied successfully to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
286
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(294 citation statements)
references
References 64 publications
2
286
0
6
Order By: Relevance
“…It was demonstrated that cell viability in the skin-like construct was above 90% in 1 week [74]. Moreover, Cubo et al created a human plasma-based bilayer skin-like tissue containing plasma-derived fibrin, fibroblasts and keratinocytes, which had successfully used for the treatment of burnt, traumatic and surgical wounds in many patients [75]. The results revealed that the printed skin-like tissue, both in vitro culture and in transplantation to immunedeficient mice, showed similar characteristics with human skin [75].…”
Section: Bioprinting Of Skinmentioning
confidence: 99%
“…It was demonstrated that cell viability in the skin-like construct was above 90% in 1 week [74]. Moreover, Cubo et al created a human plasma-based bilayer skin-like tissue containing plasma-derived fibrin, fibroblasts and keratinocytes, which had successfully used for the treatment of burnt, traumatic and surgical wounds in many patients [75]. The results revealed that the printed skin-like tissue, both in vitro culture and in transplantation to immunedeficient mice, showed similar characteristics with human skin [75].…”
Section: Bioprinting Of Skinmentioning
confidence: 99%
“…Nieves Cubo et al used primary human FBs and human KCs as well as human plasma to print a human bi‐layered skin. According to the histological and immunohistochemical in vivo and in vitro analyses, they demonstrated that the printed skin was very similar to normal human skin and successfully used the in clinical . Byoung Soo Kim et al used FBs and KCs to fabricate a human skin model with a functional transwell system by using extrusion and inkjet modules synchronously .…”
Section: Cell Selectionmentioning
confidence: 99%
“…It is more suitable for the bioprinting of 3D scaffolds in most solid organs, blood vessels, and hard tissues. The potential applied advantages of a microextrusion bioprinter make it a promising printer in the construction of bioprinting skin substitutes . Its main drawback is the low resolution (below 50 μm) and the shear stress that may affect cell viability .…”
Section: D Bioprintermentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that 3D bioprinting is a suitable technology to generate bioengineered skin for therapeutical and industrial applications in an automatized manner. [106] Koch et al selected different skin cells (fibroblasts, keratinocytes) and hMSC based on their high potential in regeneration of human skin and possible applications in stem cell therapy for their laser printing experiments. [107] This group generated a viable skin tissue free of any DNA damage.…”
Section: Bioprinted Skinmentioning
confidence: 99%